Comunidades repartidas, literaturas conectadas: (inter)nacionalismos imaginados em Cien años de soledad, de Gabriel García Márquez, e Midnight’s Children, de Salman Rushdie - Mourão, Manfred Rommel Pontes Viana (2021)
This thesis proposes two lines of reasoning: 1. the idea of nation as a divided, connected and unequal construct; and 2. This condition as a nationalist component in the construction of contemporary literatures. Initially, we searched through the Connected History, by Sanjay Subhramanyan and Serge Gruzinsky, to examine the connections between imaginaries in History and their influence on the writing of a given space, making nationalism interact with international paradigms, already evaluated by Comparative Literature recently. This line of reasoning admits nationalism as a transnational and/or planetary paradigm, as suggested by Cláudio Guillén (1985), Gayatri Chakravorty Spivak ([1993] 2003), Steven Tötösy de Zepetnek (1998) among others. Further on, specifically, we turn to a bibliography that proved to be prominent from the second half of the twentieth century and we investigate how the idea of Latin America arises and unfolds, as, prior to this conception, nationalism in independent states of the continent rival space with the great pátria grande. We observe some implications of the nation-continent dialectic, focusing on some political suggestions, whose incidence would affect the production of Latin American artistic works; among them, continental Literature, regulated by international, national and regional dictates, simultaneously, the result of the interaction of external emulators and telluric themes. The Gabriel García Márquez‘s One Hundred Years of Solitude (1967) is the object of analysis in fourth chapter, since the Colombian‘s work draws certain images about the contradictions of Latin America and imaginary limits (nation, province, etc), giving special emphasis to elements ranging from Iberian colonization, through Latin American independence, US imperialism and the idealistic downfall of the national-continental project. Therefore, we cross the continents to exemplify the interaction between national literatures, analyzing the scope of the work by García Márquez in the writing of the Midnight’s Children (1981), by Indo-British novelist Salman Rushdie; listing traits that accentuate themes and forms common to the Colombian, especially with regard to the divided nationalism of the Indian subcontinent and the political conflicts that gave rise to this imagined community. Ahead, we expose some of the scriptural influences of Eastern traditions and the Western Canon that make up an international network of literary exchanges in Rushdie‘s work. Finally, we emphasize elements of this global bazaar that focus on the World Republic of Letters, which centralizes multiple forms of production, especially emerging literatures (boom and Indian post-colonialism), through a consumer market whose contour guides some guidelines of the Literary Systems.